The Application of Mentimeter Media in Enhancing History Learning Motivation among Class X Students of SMK Negeri 1 Darul Kamal - Tifani*, Nabilla; Nurasiah, Nurasiah; Azis, Abdul (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
High learning motivation is the key to successful learning in modern education. The use of interactive technology such as Mentimeter attracts attention as a tool to increase students learning motivation. This study aims to evaluate (1) the application of Mentimeter media in learning history in class X SMK Negeri 1 Darul Kamal, and (2) whether Mentimeter media can increase the history learning motivation of students in class X SMK Negeri 1 Darul Kamal. This study used a quantitative approach with a pre-experimental research design with a one-group pretest-posttest research design. The population in this study were all students of Class X consisting of 5 classes, with a sample of Class X Tata Busana students consisting of 22 students. The sample selection in this study used purposive sampling technique. The data collection techniques included observation, questionnaire and documentation. The data analysis technique used percentage calculation, normality test, homogeneity test, and paired samples t-test. The results showed that the application of Mentimeter was in accordance with the syntax of the project-based learning model and was well implemented, with the results of the evaluation of student activity getting a score of 88% in the very good category. Then the results of the paired sample t-test analysis show tcount ttable or 11.100 2.086 at significance () = 5% (0.05) which means Ho is rejected and Ha is accepted. Thus, the application of Mentimeter media affects the history learning motivation of class X students at SMK Negeri 1 Darul Kamal, so it proves effective to be applied in learning history.